A probational experiment on directing citizens of Vilnius to libraries and its preliminary results - Vytautas Rimša (Knygotyra)
A series of experiments on directing town people to libraries was carried out under the program of sociological-psychological research on the theme "The role of libraries in developing and satisfying professional and spiritual interests of young workers." Between October 1, 1981, and December 31, 1981, a test experiment was carried out in 23 departments of the Vilnius Central Library and its branches. Its purpose was to ascertain the importance of a newspaper announcement in the form of an invitation/information in directing young workers and other categories of readers to libraries.